2009
DOI: 10.1523/jneurosci.2857-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Local and Large-Range Inhibition in Feature Detection

Abstract: Lateral inhibition is perhaps the most ubiquitous of neuronal mechanisms, having been demonstrated in early stages of processing in many different sensory pathways of both mammals and invertebrates. Recent work challenges the long-standing view that assumes that similar mechanisms operate to tune neuronal responses to higher order properties. Scant evidence for lateral inhibition exists beyond the level of the most peripheral stages of visual processing, leading to suggestions that many features of the tuning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 29 publications
5
55
0
Order By: Relevance
“…Subsequent test stimuli were drifted through the receptive field centre as determined by the initial characterization. For full details of these methods, see [31].…”
Section: Appendix a Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent test stimuli were drifted through the receptive field centre as determined by the initial characterization. For full details of these methods, see [31].…”
Section: Appendix a Methodsmentioning
confidence: 99%
“…orthogonal to the direction of travel). Above 2-38, responses are attenuated by the spatial inhibition mechanisms that define these neurons as STMDs (see [31] and review [23]). Below this size, however, as the targets fall below the receptive field size of single photoreceptors, the roll-off thus reveals contrast attenuation by the optics.…”
Section: (B) Maximum Neural Contrastmentioning
confidence: 99%
“…This raises the intriguing possibility of communication between the two neurons to mediate a simple form of visual attention. Bolzon et al (2009) showed that the simultaneous presence of a second target in the contralateral hemisphere completely suppresses the response to a target in the excitatory receptive field. In an additional experiment, they presented a second target within this excitatory region, revealing a large and diffuse inhibitory surround.…”
Section: Introductionmentioning
confidence: 99%
“…Tuned inhibition is a well explored concept in striate cortex, which provides the early stage of visual processing in the MT model. Although tuned inhibition of the EMD subunits has not been described, lateral inhibition of some form has been suggested to operate in the early stages of visual processing in insects (Srinivasan et al, 1982;Zheng et al, 2006;Bolzon et al, 2009). By contrast, a saturating output nonlinearity has often been used in models of EMDs (Zanker, 1990;Franz and Krapp, 2000).…”
Section: Discussionmentioning
confidence: 99%